Correlations of non‐alcoholic fatty liver disease and serum uric acid with subclinical atherosclerosis in obese Chinese adults: 肥胖的中国成年人非酒精性脂肪性肝病和血清尿酸与亚临床动脉粥样硬化之间的相关性研究. (11th August 2016) - Liu, Yongwen; Liu, Changqin; Shi, Xiulin; Lin, Mingzhu; Yan, Bing; Zeng, Xin; Chen, Ningning; Lu, Shuhua; Liu, Suhuan; Yang, Shuyu; Li, Xuejun; Li, Zhibin
Abstract: Background: Existing evidence about the associations of non‐alcoholic fatty liver disease (NAFLD) and serum uric acid (SUA) with subclinical atherosclerosis is controversial. The aim of the present study was to examine the associations of NAFLD and SUA with subclinical atherosclerosis. Methods: In the present cross‐sectional study, 1354 obese adults underwent hepatic ultrasonography and arteriosclerosis detection. Indices of subclinical atherosclerosis were brachial–ankle pulse wave velocity (ba‐PWV) and the ankle–brachial index (ABI). Linear regression using multivariable fractional polynomial (MFP) modeling was used to examine independent associations of NAFLD and SUA with a‐PWV and ABI. Results: Compared with controls, mean (± SD) ba‐PWV was significantly higher in subjects with NAFLD (1534 ± 292 vs 1433 ± 259 cm/s; P < 0.001) and hyperuricemia (HUA; 1519 ± 275 vs 1476 ± 287 cm/s; P = 0.007). After adjustment for sociodemographic and lifestyle factors, NAFLD and SUA were both positively related to ba‐PWV (β = 0.120 and 0.064, respectively; P < 0.05 for both). With further adjustment for insulin resistance and components of metabolic syndrome (MetS), the positive correlations were no longer significant (β = 0.017 and 0.006; P > 0.05 for both). In addition, NAFLD, but not SUA, was negatively correlated with ABI (β = −0.073; P = 0.015). Using MFP modeling, the best fractional polynomial (FP) transformation model showed that non‐linear transformations were appropriate for two variables in their relationship with ba‐PWV, namely age and fasting insulin as first‐degree FP transformations (age 3 and 1/insulin 0.5, respectively). Conclusions: Neither NAFLD nor SUA was related to ba‐PWV with increases in insulin resistance and MetS, but NAFLD was independently and negatively correlated with ABI. Highlights: The associations of NAFLD and SUA with ba‐PWV were mediated by insulin resistance and MetS, whereas NAFLD, but not SUA, was independently and negatively correlated with ABI. The present study provides evidence regarding the independent associations of NAFLD and SUA, as well as possible non‐linear relationships of continuous risk factors, with subclinical atherosclerosis.